Integration of risk management in occupational health and safety systems - Ramos, Delfina (2014)
Risk management can be considered as part of the Occupational Health and Safety System (OHS) of an organization and can be used to develop and implement the OHS policy and manage the associated risks. The success of the integration of risk management in OHS depends on both technical and human aspects. Thus, this paper presents and discusses the case of a company working in the area of solid waste treatment. This company was certified in 2009 with an Integrated Management Systems for Quality, Environment, Occupational Health and Safety. The evolution of accidents before and after the implementation of the integrated system was analysed and a questionnaire was used to capture the perceptions of the technicians on the risk management system. The analysis of the findings showed that the frequency of accidents increased since 2009 but the severity has been reduced. Several interrelated causes and consequences were analysed and discussed. Furthermore, the analysis of the opinions of the company’s technicians permitted to highlight some important aspects on the integration of risk management in the OHS system of the company. In line with this discussion some hypothesis have been formulated.